Candidate Wire Spiral Antennas for the SKA Radio Telescope - Jiwani, Aziz; Padhi, Shantanu; Waterson, Mark; Hall, Peter; Bij de Vaate, Jan Geralt (IEEE, 2012)
The SKA is a next generation radio telescope employing phased aperture arrays at its lowest operating band (SKA-low) of 70 - 450 MHz. SKA-low is a dual-polarized array consisting of antenna elements with stable impedance and low cross-polarization. We select the well-known broadband conical spiral antenna and its dual-polarized derivative to be evaluated as candidate elements for SKA-low. Previously, we evaluated the sheet version of the conical spiral and found that it maintained well its broadband characteristics. Looking towards ease of manufacturing, we now evaluate wire versions of the designs. We find that the single-polarized wire version has stable impedance and low cross-polarization from 150 - 450 MHz. However, at low frequencies the cross polarization increases. The dual-polarized version maintains its characteristics over a small band but with higher (> -20 dB) cross polarizations. Measured results confirm the simulated antenna behavior.